Hans Paasche (1881-1920) et le féminin - Camille Auboin (Recherches Germaniques)
Questioning the notion of female gender in Germany around 1900 implies considering the interaction of several geographical spaces. The colony was no virgin territory to be modelled on the image of the metropolis. On the contrary it proved to be a space in which European certainties got questioned or even negated. In the third letter of Hans Paasche’s (1881-1920) epistolary novel Die Forschungsreise des Afrikaners Lukanga Mukara ins innerste Deutschland (1912) the detour through the narrative prism of the African conveys a sharp criticism of the European norms and practices of the feminine and invites to rethink them. By elaborating a ‘healthier’, a more ‘natural’ and ‘authentic’ Idea of the feminine obviously inspired by the fantasy model of the African woman, Paasche’s text highlights the utopian foundations shared by life-reform-movements (Lebensreformbewegungen) and colonial imaginations.